جمالية أسلوب التقديم و التأخير في شعر عاشور فني - حملاوي, ليلى; ملوك, رابح (جامعة الوادي - university of Eloued, 2021)
الجملة هي أصغر وحدة في اللغة العربية تبنى عليها الدراسات النحوية والبلاغية، وتخضع هذه الجملة إلى قوانين و ضوابط تحفظ لها رتب كلماتها، إلا أن الشاعر استطاع كسر قيود هذه الحتمية باللجوء إلى أسلوب التقديم و التأخير للتعبير عن مشاعره وأحاسيسه . يعد أسلوب التقديم و التأخير من أهم الأساليب اللغوية التي تكسب اللغة العربية المرونة والطواعية، حيث تسمح للمتكلم أن يتحرك بكل حرية متخطيا كل الرتب المحفوظة والعدول عن هذه الرتب يمثل الخروج عن اللغة المألوفة إلى لغة الإبداع و الجمال، و الشاعر الجزائري عاشور فني تفنن في توظيف أسلوب التقديم و التأخير في دواوينه الشعرية. و في بحثنا هذا نحاول رصد مواطن التقديم و التأخير بكل أنواعه في شعر عاشور فني كما نحاول الكشف عن الأثر الجمالي الذي كسا شعره رونقا. متبعين في ذلك منهج الإجصاء و التحليل. Abstract: The sentence is the smallest unit in the Arabic language upon which grammatical and rhetorical studies are built, and this sentence is subject to rules and regulations that preserve the order of its words, but the poet could break the limitations of this determinism by resorting to the ‘inversion’ method to express his emotions and feelings. The ‘inversion’ method is one of the most important linguistic methods that allowed the Arabic language to gain flexibility and voluntary, as it allows the speaker to move freely, bypassing all the saved ranks, and abandoning these ranks represents a departure from the familiar language to the language of creativity and beauty, and the Algerian poet Ashour Fani artistically outrivaled in employing the ‘inversion’ method in his poetry divans. In our research, we try to monitor the ‘inversion’ areas of all kinds in Ashour Fen0ni’s poetry, as we try to reveal the aesthetic impact that arrayed his poetry with luster, using for that the of statistics and analysis method.
مقال
Keywords: التقديم – التأخير – الجمال – الجملة – التركيب – الأسلوب